A Hybrid Opportunistic IoT Secure Routing Strategy Based on Node Intimacy and Trust Value. (9th February 2022) - Yu, Lin; Xu, Gang; Wang, ZhiFei; Zhang, Na; Wei, FengQi
Abstract : Routing strategy is one of the most important researches in Opportunistic Internet of Things (IoT), and it highly influences the efficiency of data transmission. In this paper, a hybrid Opportunistic IoT secure routing strategy based on node intimacy and trust value (HIRouter) is proposed to resolve the problem of unbalanced transmission efficiency and security in the message delivery process. According to the records of node encounter and message forwarding, the strategy proposed in this paper can calculate nodes' intimacy and trust value. The messages are then forwarded based on the intimacy and trust value between nodes. Experimental results verify that HIRouter algorithm we proposed can improve the message delivery rates and reduce the overhead rate in the Opportunistic IoT with dense nodes and frequent interactions between nodes.